2019
DOI: 10.1111/jhn.12683
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of isoflavones is associated with a lower prevalence of subclinical cardiovascular disease in postmenopausal women: cross‐sectional study

Abstract: Background: Menopause has been associated with an increased risk of cardiovascular disease. It has been shown that isoflavones protect vascular endothelial cells against induced oxidative stress injury. Therefore, the present study aimed to investigate the association between the dietary intake of isoflavones and the presence of subclinical cardiovascular disease (CVD) in postmenopausal women. Methods: Ninety-six postmenopausal women [mean (SD) age 55.2 (4.9) years, body mass index (BMI) 27.2 (4.6) kg m À2 ] c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…These results are reasonable, because it is known that bioavailability of epicatechin and isoflavones is relatively higher than that of C3G and procyanidins [ 33 , 34 ], indicating that epicatechin and isoflavones in black soybean are considerable active compounds for the improvement of vascular function though possessing their antioxidant activity. It is known that soy isoflavones improves vascular functions [ 35 , 36 ]. Interestingly, certain amounts of isoflavones were detected as their aglycone forms in plasma and urine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results are reasonable, because it is known that bioavailability of epicatechin and isoflavones is relatively higher than that of C3G and procyanidins [ 33 , 34 ], indicating that epicatechin and isoflavones in black soybean are considerable active compounds for the improvement of vascular function though possessing their antioxidant activity. It is known that soy isoflavones improves vascular functions [ 35 , 36 ]. Interestingly, certain amounts of isoflavones were detected as their aglycone forms in plasma and urine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship has been found between isoflavone intake, endothelial function and reduced lower carotid atherosclerotic burden [ 161 ]. Ferreira and colleagues also found that higher isoflavone intake was independently associated with lower risk for subclinical CVD in menopausal women [ 162 ]. Results from experimental studies using phytoestrogens for CVD prevention and treatment have been mixed, but generally positive.…”
Section: Phytoestrogensmentioning
confidence: 99%
“…In addition, we recently reported higher isoflavone dietary intake may be associated with lower risk of subclinical CVD, as assessed by CCA-IMT status, independently of endogenous estradiol levels and BMI [ 94 ]. Isoflavones might have beneficial effects by its anti-inflammatory and antioxidant properties, through the production of equol, an active metabolite formed from daidzin/daidzein by gut microbiota [ 95 ].…”
Section: Dietary Intake and Clinical Endpoints In Menopausal Womenmentioning
confidence: 99%